Sacrificial Cathodic Protection Method of Reinforcement from Corrosion (International Journal of Innovative Research in Engineering & Management, 2023)
Cathodic protection prevents corrosion of  steel incorporated in concrete structures and bridges.  Because of the action of chloride ions, reinforced structures  readily corroded in a maritime environment. For the majority  of concrete structures, Cathodic Protection offers long-term  rehabilitation techniques. Due to the corrosion of the  reinforcing steel, concrete structures exposed to marine  conditions are deteriorating. Effective corrosion protection  must be taken into consideration for both new construction  and damage repair because this deterioration progresses  quickly and seriously. For all concrete structures in marine  conditions, cathodic protection is anticipated to be a realistic  corrosion protection method. The following factors were  taken into account in this study to establish high reliability  for cathodic protection of concrete structures: (1)  establishing standards for cathodic protection on concrete  structures (2) analysing the issue of overprotection in  prestressed concrete constructions.
Keywords: Concrete; Reinforcement; Corrosion Protection; Safety Critical Element